Incidence of H1N1 in pediatric population in a tertiary care hospital in Bangalore - Dr. Mahantesh.S; Dr. Manasa.S (Tropical Journal of Pathology and Microbiology, 2017)
Objectives: Influenza viruses continue to be a major health threat in both endemic and pandemic forms. The rapid, continuous, and unpredictable nature of influenza viral evolution makes vaccine strategies and pandemic planning difficult .In elderly, infants and in people with chronic diseases, influenza is associated with high mortality. As there are very limited studies relating to Influenza A H1N1 and its epidemiology in the pediatric population, this study was done to study the clinical and epidemiological profile of patients found positive for Influenza A H1N1 in pediatric population in a tertiary care hospital in Bangalore. Materials and methods: This is a retrospective study done over a period of 6 months from January 2017 to June 2017. The study population included all the suspected patients tested for Influenza A H1N1 by real-time RT-PCR. Results: Total of 89 patients were tested for Influenza A H1N1 out of which 31(34.8%) were positive. The most common symptoms were fever (87.6%), cough (49.77%), sore throat (27%) and breathlessness (23.9%). Maximum cases were detected in the 0-5 years age group in that 19(61.2%) were positive, followed by 15-18 yrs in which 23(25.8%) were tested in which 9(29.03%) were positive. Influenza A H1N1 resulted in death of 3(3.3%) of the total admitted suspected H1N1 cases in our hospital. Conclusion: On the basis of these findings, it can be concluded that prevalence of Influenza A H1N1 is high in children with the age group of 0-5yrs. The age shift of severe influenza A (H1N1) towards younger children may be explained by increasing immunity in the older pediatric population.